Transport Sector CO(2) Emissions Growth in Asia : Underlying Factors and Policy Options - Timilsina, G. R. (2012)
This study analyze the potential factors influencing the growth of transport sector carbon dioxide (CO(2)) emissions in selected Asian countries during the 1980-2005 period by decomposing annual emissions growth into components representing changes in fuel mix, modal shift, per capita gross domestic product (GDP) and population, as well as changes in emission coefficients and transportation energy intensity. We find that changes in per capita GDP, population growth and transportation energy intensity are the main factors driving transport sector CO(2) emission growth in the countries considered. While growth in per capita income and population are responsible for the increasing trend of transport sector CO(2) emissions in China, India, Indonesia, Republic of Korea, Malaysia, Pakistan, Sri Lanka and Thailand; the decline of transportation energy intensity is driving CO(2) emissions down in Mongolia. Per capita GDP, population and transportation energy intensity effects are all found responsible for transport sector CO(2) emissions growth in Bangladesh, the Philippines and Vietnam. The study also reviews existing government policies to limit CO(2) emissions growth, such as fiscal instruments, fuel economy standards and policies to encourage switching to less emission intensive fuels and transportation modes. (C) 2009 Elsevier Ltd. All rights reserved.